2015
DOI: 10.1111/imm.12543
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate differentially regulates the polarization of differentiating and differentiated macrophages

Abstract: SummaryThe tissue accumulation of M1 macrophages in patients with metabolic diseases such as obesity and type 2 diabetes mellitus has been well-documented. Interestingly, it is an accumulation of M2 macrophages that is observed in the adipose, liver and lung tissues, as well as in the circulation, of patients who have had major traumas such as a burn injury or sepsis; however, the trigger for the M2 polarization observed in these patients has not yet been identified. In the current study, we explored the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
5
26
0
Order By: Relevance
“…Also, evidence is found that high doses of palmitate significantly influence the differentiation of bone marrow‐derived macrophages and promote the anti‐inflammatory M2‐subtype. In already differentiated macrophages, palmitate shows proinflammatory responses (Xiu, Diao, Qi, Catapano, & Jeschke, ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, evidence is found that high doses of palmitate significantly influence the differentiation of bone marrow‐derived macrophages and promote the anti‐inflammatory M2‐subtype. In already differentiated macrophages, palmitate shows proinflammatory responses (Xiu, Diao, Qi, Catapano, & Jeschke, ).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that IL-6 induces preferential mobilization of saturated FFAs over unsaturated lipid species, which are important components in the inflammatory cascade. Alternatively, we recently found that chronic exposure to palmitate induces M2 macrophage differentiation in adipose tissue, which dampens inflammation and facilitates tissue repair27. Therefore, SFAs may in fact contribute to anti-inflammatory activation in select clinical contexts, contrary to its long-established role as a pro-inflammatory lipid species.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidations or metabolites of fatty acids promote macrophages differentiating into the M2 subtype 45 , whereas circulating levels of free fatty acids elevate the populations of M1 subtypes 46 . Moreover, chronic treatment with palmitate decreases phagocytosis and inhibits the production of proinflammatory cytokines 47 . In the present study, the in-vitro macrophage differentiation model is established to observe the alternations of macrophages in an Intralipid-containing environment.…”
Section: Scientific Reports |mentioning
confidence: 99%